2014
DOI: 10.1007/s13197-014-1649-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whey and casein protein hydrolysates on rheological, textural and sensory properties of cookies

Abstract: Milk proteins were hydrolyzed by papain and their effect on the rheological, textural and sensory properties of cookies were investigated. Water absorption (%) decreased significantly as the amount of milk protein concentrates and hydrolysates increased up to a level of 15 % in the wheat flour. Dough extensibility decreased with inrease in parental proteins and their hydrolysates in wheat flour, significantly. Similarly, the pasting properties also varied significantly in direct proportion to the quantity adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 22 publications
(21 reference statements)
1
43
2
8
Order By: Relevance
“…The lemon biscuits, being a baked product, had a structure with little moisture which made them very resistant, hard, rigid and compact. Similar results were found Gani et al, [28], in baked biscuits, which indicated that among the factors that most contributed to and influenced the textural parameters were gelatinisation of starches, reduction of moisture content of the product during heat treatment, denaturation of proteins and crystallization of sugar at baking temperature. In figures 7, 8, 9, and 10, the behaviour of a random sample of lemon cracker for each thickness was observed in detail during the respective three-point cracking tests.…”
Section: Proximal Composition Of Biscuit Samplessupporting
confidence: 87%
“…The lemon biscuits, being a baked product, had a structure with little moisture which made them very resistant, hard, rigid and compact. Similar results were found Gani et al, [28], in baked biscuits, which indicated that among the factors that most contributed to and influenced the textural parameters were gelatinisation of starches, reduction of moisture content of the product during heat treatment, denaturation of proteins and crystallization of sugar at baking temperature. In figures 7, 8, 9, and 10, the behaviour of a random sample of lemon cracker for each thickness was observed in detail during the respective three-point cracking tests.…”
Section: Proximal Composition Of Biscuit Samplessupporting
confidence: 87%
“…Cookies with GP presented higher hardness than the control, being this difference was more pronounced with increasing substitution percentage. Other authors also observed an increment of hardness with the addition of rice bran protein (Yadav et al ., ) or dairy proteins (Gani et al ., ; Sarabhai & Prabhasankar, ). This effect aligns with the results of Pareyt et al .…”
Section: Resultsmentioning
confidence: 99%
“…Changes in cookies colour are produced due to Maillard reactions between reducing sugars and amino side chains of proteins (Wani et al, 2010;P erez et al, 2013). Protein hydrolysis produces particles with smaller size, thereby increasing the number of reactive sites, which leads to greater surface available to interact with reducing sugars (Gani et al, 2015). This may explain the lower L* values of the cookies with HGP.…”
Section: Colourmentioning
confidence: 99%
“…Protein hydrolysates have been widely produced and characterized from the enzymatic hydrolysis of various proteins, and their functional and biological properties have been extensively investigated in the literature (Zheng et al 2015;Cian et al 2015;Chalamaiah et al 2015a;Gani et al 2014;Cattaneo et al 2014).…”
Section: Introductionmentioning
confidence: 99%